552 Benign Pilomatricoma with Osseous Metaplasia: A Rare Case. (19th August 2022) - Bhatti, N; Ramchandani, J; Chong, W; August, S
Abstract: Pilomatricomas are a frequently misdiagnosed benign neoplasm of the skin derived from hair matrix cells. Pilomatricomas may undergo calcification and ossification although the latter is rare and poorly documented, with only eight cases reported since 2006. We present a case of pilomatricoma with osseous metaplasia arising from the scalp in an 87-year-old female patient. She was referred by her general practitioner via the two-week pathway, for a suspicious lesion. On examination, there was a 2×1cm nodule, with protruding hardened yellow sebaceous material, on the right side of the patient's occipital scalp. The lump was hard, non-tender and had been present for 17 years. The surrounding area was bleeding and slightly ulcerated. A clinical diagnosis of a ruptured epidermal cyst was made, and the patient was prepared for excision under local anaesthetic. The excised lesion of 23×18×10mm with 22×9mm of skin was sent for histology. This revealed a partially ulcerated dermal lesion composed of islands of keratin with 'ghost cell' outlines. Foreign body granulomas, transition to mature lamellar bone and foci of calcification were noted. There were no definite populations of basaloid cells and features of malignancy were not seen. These findings are consistent with benign pilomatricoma with osseous metaplasia. The patient was discharged 4 weeks later with satisfactory wound healing. Differentiating this tumour from other commonly encountered benign masses remains a challenge, as seen in this case which was initially mis-diagnosed as a ruptured epidermal cyst.